Human Induced Pluripotent Stem Cell and Nanotechnology-Based Therapeutics. Issue 11 (November 2015) - Liu, Wei-Hsiu; Chang, Yuh-Lih; Lo, Wen-Liang; Li, Hsin-Yang; Hsiao, Chia-Wei; Peng, Chi-Hsien; Chiou, Shih-Hwa; Ma, Hsin-I; Chen, Shih-Jen
Human induced pluripotent stem cells (hiPSCs) can be genetically reprogrammed to an embryonic stem cell-like state and can provide promising medical applications, such as diagnosis, prognosis, drug screening for therapeutical development, and monitoring disease progression. Despite myriad advances, traditional viral-based reprogramming for generating hiPSCs has safety risks that hinder further practical applications of hiPSCs. In the past decade, nonviral-based reprogramming has been used as an alternative to produce hiPSCs and enhance their differentiation. In addition, the efficiency of nonviral-based reprogramming is generally poor, compared to that of viral-based reprogramming. Recent studies in nanoscale-structured particles have made progress in addressing many applications of hiPSCs for clinical practice. The combination of hiPSCs and nanotechnology will actually act as the therapeutic platform for personalized medicine and can be the remedies against various diseases in the future. In this article, we review recent advances in cellular reprogramming and hiPSC-related research, such as cell source, delivery system, and direct reprogramming, as well as some of its potential clinical applications, including mitochondrial and retinal disease. We also briefly summarize the current incorporation of nanotechnology in patient-specific hiPSCs for future treatments.